Реализация модели и инженерной методики обеспечения температурного режима ЭА оптимизацией теплообмена конструкции с окружающей средой - Азаренков, Владимир Ильич; Куценко, Александр Сергеевич (Технологический центр, 2012)
На основе решения уравнения теплопроводности для прямоугольного параллелепипеда с аналогичными источниками тепла, предлагается инженерная методика проектирования конструкции радиоэлектронной аппаратуры, исходя из заданного температурного режима изделия.

Based on the solution of the heat equation for a rectangular parallelepiped with similar heat sources and taking into account specified thermal condition of a product, an engineering method for radio-electronic equipment structural design is presented. Allowable or maximum operating temperature, cooling method, reliability, weight, geometric construction or the final cost of the product may all act as limiting factors. A dynamic programming method was used to determine the optimal heat transfer coefficients between the faces of the heated zone and the surrounding medium. The search for ultimate solution gives ground for technical devices design, i.e. the construction design values, which would allow to create products that meet the specified thermal criteria requirements without major rework.
Keywords: моделирование; тепловой режим; оптимизация теплообмена; коэффициент теплообмена; источник тепла; изделие; modeling; thermal condition; heat exchange optimization